PENGARUH KOMITMEN ORGANISASI DAN KOMPETENSI PEGAWAI TERHADAP KINERJA PEGAWAI UPT. PERLINDUNGAN DINAS TANAMAN PANGAN DAN HOLTIKULTURA PROVINSI RIAU - Martha Angelina; Susi Hendriani; Restu Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine how the variables influence Organizational Commitment and Employee Competency simultaneously and partially to UPT. Protection of Food Crops and Horticulture Department of Provincial Riau. There was the sample in this study were 68 employees. Analysis of the data used is descriptive analysis, as it also uses quantitative analysis of multiple linear analysis with SPSS version 17. The test data shows that the variable organizational commitment and competence of the employees have a significant effect on employee performance.Keywords: Organizational Commitment, Competence Employees, Employee Performance